Pengaruh Capital Adequacy Ratio, Beban Operasional dan Pendapatan Operasional, Loan To Deposit Ratio, dan Non Performing Loan Terhadap Profitabilitas Perbankan - Dwi Damayanti, Atisyah; Indrabudiman, Amir (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research was conducted aiming to determine the Effect of Capital Adequacy Rasio, Operational Expenses and Operational Income, Loan to Deposit Ratio, and Non-Performing Loans on Profitability. This research was conducted on companies in the banking sub-sector listed on the Indonesia Stock Exchange (IDX) with a research period of 2019 – 2023. The sampling technique in this study used purposive sampling with a sample size of 38 banks that met the criteria. The data analysis used in this study was multiple linear regression analysis using a statistical test tool, namely SPSS version 22.0. The conclusion of the study regarding Operational Expenses and Operational Income, Loan to Deposit Ratio, Non-Performing Loans have a negative and significant influence on profitability, while Capital Adequacy Ratio does not effect on profitability.